Zearalenone causes embryotoxicity and induces oxidative stress and apoptosis in differentiated human embryonic stem cells. (February 2019) - Cao, Hanwen; Zhi, Yuan; Xu, Haibin; Fang, Haiqin; Jia, Xudong
Abstract: In this study, murine embryonic stem cell test (mEST) and human embryonic stem cell test (hEST) models were developed to evaluate the embryonic toxicity of Zearalenone (ZEN) according to the methods established in our laboratory. The embryotoxicity of ZEN was described by comparing the three functions calculated based on three endpoints, that is, 50% inhibitory proliferation concentration (IC50 ) of embryonic stem cells (ESCs) and 3T3 cells and 50% inhibition of cardiomyocyte differentiation (ID50 ) of ESCs determined in the EST model. Moreover, differentiation of human embryonic stem cell (hESC) was initiated by embryoid bodies (EBs) formation; EBs were exposed to different concentrations of ZEN for 24 h to detect cellular reactive oxygen species (ROS) generation, the mitochondrial transmembrane potential (MMP), apoptosis, cell cycle, and the related protein expression. Based on the results of the three endpoints and functions of ZEN in mEST and hEST, ZEN was evaluated to have strong embryonic toxicity both by two models. The increases in cellular ROS and loss of MMP were observed at 2 and 4 μg/ml concentrations. Flow cytometry showed that ZEN induced cell cycle arrest and apoptosis. The upregulation of p53, caspase-9, caspase-3, and the ratio of Bax/Bcl-2 were observed at 2 and 4 μg/ml concentrations. Collectively these results demonstrate that ZEN has strong embryonic toxicity and induces oxidative stress and apoptosis in differentiated human ESCs. Highlights: ZEN was evaluated to have strong embryo toxicity both by mEST and hEST. ZEN caused oxidative stress in differentiated H9-hESCs. ZEN induced apoptosis in differentiated H9-hESCs.